THE FACTORS THAT INFLUENCE THE CHOICE OF GROUP WORK’S SOCIAL WORK METHODS OF THERAPEUTIC COMMUNITY AND NARCOTIC ANONYMOUS MODEL IN THE SOCIAL REHABILITATION CENTER FOR DRUG ADDICTION - Fajar Utama Ritonga; Adil Arifin, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
This research aims to determine the factors that influence the choice of group work’s social work methods of therapeutic community (TC) and narcotics anonymous (NA) model in the social rehabilitation center for drug addiction i. The research method is a descriptive qualitative approach, the key informants are the owners of the orphanage or program managers as well as the policymakers in the social rehabilitation center for drug addiction. The main informants are social workers and counselors and staff in the social rehabilitation center. The data collection technique uses in-depth interviews and focuses on group discussions. The data analysis technique uses component analysis. Research locations is in Medan Community Partners Foundation (YAMIMAS Medan), Caritas Shelter House PSE in Medan City, Loka BNN (National Narcotic Agency) in Kabupaten Deliserdang, Permadi PutraSocial Institution ‘INSYAF’ in Kabupaten Deliserdang, Nazar Foundation in Medan. The research results are; the internal factors: for the private institution's influence by the self-desire or by joint decisions are based on careful consideration of the managers or administrators of social rehabilitation institution. For the government-owned orphanages, the choice of therapeutic community model decides by the ministry of social affairs and the national narcotics agency. The external factors: for the private institution's influence by the pieces of information from national and international seminars, or experiences in dealing with drug clients/resident, social workers, and counselors who are struggling to use therapeutic community and narcotic anonymous group work model and sharing of experiences from administrators or manager of other social rehabilitation institution. Meanwhile, institutions under the ownership of the government are not influenced by external factors because they only carry out an order from the ministry of social affairs or national narcotics agency.